2020
DOI: 10.1111/1475-4932.12537
|View full text |Cite
|
Sign up to set email alerts
|

A Model of the Australian Housing Market

Abstract: We build an empirical model of the Australian housing market that quantifies interrelationships between construction, vacancies, rents and prices. We find that low interest rates (partly reflecting lower world long‐term rates) explain much of the rapid growth in housing prices and construction over the past few years. Another demand factor, high immigration, also helps explain the tight housing market and rapid growth in rents in the late 2000s. A large part of the effect of interest rates on dwelling investme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
(40 reference statements)
1
11
0
Order By: Relevance
“…financial liberalisation, increasing household debt, residential mortgage-backed securitisation) that have led to the current dynamics, but how these have interacted with shifts in multiple other policy spheres. 2 Our findings also challenge the economic narrative that rising house prices are primarily driven by the long-term fall in real interest rates creating a divergence between rents and prices (Weeken, 2004;Miles and Monro, 2019;Saunders and Tulip, 2019). Instead, we find that low rates are a necessary, but not sufficient, condition for high house prices.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…financial liberalisation, increasing household debt, residential mortgage-backed securitisation) that have led to the current dynamics, but how these have interacted with shifts in multiple other policy spheres. 2 Our findings also challenge the economic narrative that rising house prices are primarily driven by the long-term fall in real interest rates creating a divergence between rents and prices (Weeken, 2004;Miles and Monro, 2019;Saunders and Tulip, 2019). Instead, we find that low rates are a necessary, but not sufficient, condition for high house prices.…”
Section: Introductionsupporting
confidence: 54%
“…One argument that has recently come to the fore is that it is low real interest rates -rather than financial liberalisation or supportive tax policies -that are the key demand-side driver of housing and house prices (Saunders and Tulip, 2019; and see Miles and Monro, 2019 for the UK case).…”
Section: Discussion and Alternative Policy Directionsmentioning
confidence: 99%
“…In Australia, Saunders and Tulip (2019) analysed the interrelationships between construction, vacancies, rents and prices in the Australian housing market, and conclude that rapid growth in housing prices and construction can be attributed to low interest rates. Sutton, Mihaljek et al (2017) estimated the response of house prices to changes in short-term and long-term interest rates in 47 advanced and emerging market economies and found that short-term interest rates are an important driver of house prices in most countries, especially the USA.…”
Section: Interest Ratesmentioning
confidence: 99%
“…The persistence in housing service inflation that we found using our model, and which drives our conclusion, is also observed in less structured estimation exercises. For example, Saunders and Tulip (2019) find that rents and house prices are significantly explained by their own momentum in an analysis using a semi-structural econometric model. In fact, they note that rents are unusually easy to forecast due to their persistence.…”
Section: Commodity Prices and Housing Investmentmentioning
confidence: 99%